Post-earthquake quality of life among students - Rusmini Rusmini; Lale Wisnu Andrayani; Hamdan Hariawan (International Journal of Public Health Science (IJPHS), 2020)
Quality of life is one of the many psychological impacts of post-disaster. One of the impacts of the North Lombok earthquake in 2018 was that many school buildings and residences were damaged and collapsed. This research aimed to determine the quality of life of boarders and public students displaced after the earthquake in North Lombok. This research was comparative research with cross-sectional design. The samples of this research were 85 students consist of 40 students of emergency public school and 45 students of emergency Islamic boarding school. This research variable was the quality of life of boarders and public students. Measurement of this study using KIDSCREEN-27 and analyzed by bivariate and multivariate analysis with the value of α<0.05. This study showed the quality of life for boarders students higher than public students (p=0.008).